2021
DOI: 10.31436/imjm.v20i4.1911
|View full text |Cite
|
Sign up to set email alerts
|

Does Personality and Anxiety Symptomatology Matter in the Diabetes Mellitus Treatment Adherence? A Cross-Sectional Study Among Women with Diabetes Mellitus.

Abstract: Abstract Purpose: Anxiety is prevalent among women with diabetes mellitus. Women also tend to have higher levels of neuroticism and anxiety. These symptoms can have an impact on social functioning and diabetes care. The main aim of the present study was to determine the relationship between neuroticism and anxiety symptoms, and other clinical and psychosocial variables, among women with diabetes mellitus (DM). Patients and methods: This was a cross-sectional study conducted on women with diabetes m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…In the cross-sectional study, Woon et al [20] studied The Big-Five Personality Traits and Quality of Life in Elderly Malaysian Patients with Diabetes Mellitus. The results of the study, they undoubtedly confirmed the hypothesis that personality traits may play an important role in moderating the impact of diabetes on patientsʹ lives, even among elderly diabetic patients who were likely to have lived with the disease for a long time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cross-sectional study, Woon et al [20] studied The Big-Five Personality Traits and Quality of Life in Elderly Malaysian Patients with Diabetes Mellitus. The results of the study, they undoubtedly confirmed the hypothesis that personality traits may play an important role in moderating the impact of diabetes on patientsʹ lives, even among elderly diabetic patients who were likely to have lived with the disease for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Traits such as conscientiousness and agreeableness may act as protective factors for the ʹQuality of lifeʹ variable in older patients with diabetes, while the trait of neuroticism may potentially be a risk factor for reduced ʹQuality of lifeʹ in these patients [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the cross-sectional study, Woon et al [34] studied the Big Five Personality Traits and Quality of Life in Elderly Malaysian Patients with Diabetes Mellitus. The results of the study undoubtedly confirmed the hypothesis that personality traits may play an important role in moderating the impact of diabetes on patients' lives, even among elderly diabetic patients who were likely to have lived with the disease for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Traits such as conscientiousness and agreeableness may act as protective factors for the 'Quality of life' variable in older patients with diabetes, while the trait of neuroticism may potentially be a risk factor for reduced 'Quality of life' in these patients [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation